The Selection of Whether to Enter the University or the University Institute of Technology is a Decision that Displays One's Attitude toward Knowledge - Supala, Supala (Darul Yasin Al Sys, 2023)
For the past fifty years, the dynamics of guidance have been at the centre of social, political and educational concerns. Many researchers have conceptualized the determinants at work in the development of orientation choices: Bourdieu and Passeron adopt a sociological point of view with their model of social reproduction, while others develop this process of orientation from a more psychological angle, notably with the notion. We wish to contribute to the effort to build knowledge by developing an explanatory model of career choices at the time of entry into higher education. This study involves 265 participants, including 147 students enrolled in the first year of IUT GEA and 118 students enrolled in the first year of an AES degree at the university. There are sociobiographical differences between our two populations. Not surprisingly, our population comes from a higher socio-professional background. For both AES and GEA, the father's level of education is mostly equal to or higher than the baccalaureate with percentages of 56.5% and 66.9% respectively (χ2(2) = 4.25, p = .04). This is also the case for the mother's level of education, with percentages of 57.4% and 67.6% respectively (χ2(2) = 12.68, p = .01). These results also show us that the level of education of both fathers and mothers is, in each case, higher for GEA students The results of this research allow us to affirm that the choices of orientation in the IUT GEA or at the university section AES at the time of entry into higher education are determined by the interrelation of socio-biographical and psychological differences. In particular, this study reveals important distinctions between these two categories of students in their forms of relationship to knowledge, differences that explain their choices of orientation. These choices underpin the projection of the individual into his or her future professional and social integration. However, the position he hopes to occupy in the training landscape, and in particular his sector, suggests a number of future social and professional positions that will be